PENEGAKAN HUKUM DI INDONESIA DALAM ERA TINGGAL LANDAS - Komariah, Komariah (Jurnal Bestari, 1992)
Democratic countries usually based on law as the "supreme" legislator. As one of those who held democracy as the state of mind for nation building, Indonesia was more popular as the rechstaat than the machstaat. Unfortunately, in many cases, the style of Indonesian life did not step on the rule of life of law. We saw injustices in some events of institutional life. To reach the objectives of the take off period, the rule of law must be realized as the main pillars.